The Relationship between Curriculum Administration Competencies and Teacher Learning Management with the Effectiveness of the Administration of Educational Institutions under the Secondary Educational Service Area Office Bangkok 1 Group 6 - Phukchit, Sirikhuan; Sithithul, Trairat; Chedsadawarangkul, Thanika (Wishing Journal Review, 2025)
Abstract Teachers’ competency in curriculum administration and learning management is the heart of teaching and learning in educational institutions. According to the Basic Education Core Curriculum and the National Education Act but from reporting the results of the Ordinary National Educational Test (O-NET) at Mathayom 6 level, it was found that schools under the Office of Secondary Educational Service Area Bangkok, Area 1, Group 6, when comparing the average scores of 5 learning subject groups, academic year 2020, had an average score lower than the standard criteria. Therefore, as the researcher is such educational personnel. that is responsible for teaching and learning which is the most important part that affects the effectiveness of the educational institution Therefore, he is interested in studying the topic. The relationship between curriculum administration competencies and teacher learning management with the effectiveness of educational institutions under the Secondary Educational Service Area Office Bangkok 1 Group 6, with the objectives to 1) study the level of competency in curriculum administration and learning management of teachers, 2) study the effectiveness level of educational institutions, and 3) to study the relationship between administrative competency Curriculum and teacher learning management and administrative effectiveness of educational institutions. This research is quantitative research. The sample used in the research is educational institution administrators and teachers of schools under the Bangkok Secondary Educational Service Area Office, Area 1, Group 6, Academic Year 2021, totaling 256 people, 13 educational institution administrators and 243 teachers obtained from the calculation. Yamane’s formula for finding the proportion of teachers in each school. The research instrument was a 5-level rating scale questionnaire with a confidence value of 0.95. Statistics used in data analysis included percentages, means, and standard deviations. and Pearson’s product moment correlation coefficient The results of the research found that 1) teachers’ curriculum administration and learning management competencies Under the jurisdiction of the Secondary Educational Service Area Office Bangkok 1 Group 6, the overall level was at a high level in every aspect (x̅ = 4.30). When considering each aspect, it was found that Teachers’ competency in curriculum administration and learning management Under the jurisdiction of Secondary Educational Service Area Office Bangkok 1 Group 6, it is at a high level. sorted by arithmetic mean From highest to lowest, the measurement and evaluation of learning outcomes (x̅ = 4.34) the use and development of innovations. Technology for learning management (x̅ = 4.32) in terms of knowledge, ability to design learning (x̅ = 4.29) and in creating and developing curriculum (x̅ = 4.28), respectively. 2) Effectiveness of the administration of educational institutions. Under the jurisdiction of the Secondary Educational Service Area Office Bangkok 1 Group 6, the overall level is at a high level in all aspects (x̅ = 4.32). When considering each aspect, it was found that Effectiveness of the administration of educational institutions Under the jurisdiction of the Secondary Educational Service Area Office Bangkok 1 Group 6, it is at a high level. sorted by arithmetic mean From highest to lowest, personnel have standards (x̅ = 4.36), promoting discipline among students (x̅ = 4.34), atmosphere supporting student learning (x̅ = 4.33), improving student academic achievement (x̅ = 4.32). Monitoring and supervising the teaching and learning process (x̅ = 4.29) and arranging the working environment and welfare (x̅ = 4.28), respectively, and 3) the relationship between teachers’ curriculum and learning management competencies and the effectiveness of educational institution administration. Under the Secondary Educational Service Area Office Bangkok 1 Group 6, there is a high positive relationship (rxy= 0.83) with statistical significance at 0.05. The results of this research found that teachers’ curriculum administration and learning management competencies Under the jurisdiction of the Bangkok Secondary Educational Service Area Office, Area 1, Group 6, in the area of curriculum creation and development, activities should be organized to promote skills in curriculum creation and development. and encourage educational institutions to work together with communities, temples, agencies, and educational institutions in both the public and private sectors. Respond to social and economic changes Effectiveness of the administration of educational institutions educational institution administrators in schools under the Bangkok Secondary Educational Service Area Office, Area 1, Group 6 should promote the provision of working environments and welfare. A desirable working atmosphere is created to create morale and encouragement for working together. Make personnel satisfied with their work and the results of the analysis of the relationship between teachers’ curriculum administration and learning management competencies and the administrative effectiveness of educational institutions. Educational institution administrators should promote and support, organize training, as well as provide lecturers with expertise in student-centered learning management for teachers and educational personnel. To develop the ability to design learning that is student-centered. Organize activities that allow students to learn the thinking process and problem-solving process and be able to apply knowledge in daily life. which from the results of this research educational institutions under the Bangkok Secondary Educational Service Area Office, Area 1, Group 6, may need to consider factors affecting competency in curriculum administration and learning management. and factors affecting the effectiveness of the administration of educational institutions in other areas in order to develop teachers’ competencies. and guidelines for managing educational institutions to be more effective.